Cardiac Valve Involvement in Rheumatoid Arthritis: A Case-Control Study Among Adult Patients in Sulaimaniyah Province - Hadi, Krmanj Mohammed; Mirza, Raouf Rahim; Saeedq, Dana Hama Baqi Mohammed; Ahmed, Farman Abdullah (Sulaimani Journal for Pure and Applied Sciences, 2023)
Background: The frequency of valvular heart disease (VHD) among rheumatoid arthritis (RA) patients varies in the literature ranging between 3-70%. This considerable variability might be attributed to the examined population's varied genetic backgrounds and the different methodologies utilized to identify valvular disease. VHD resulting in severe symptomatic aortic insufficiency is an uncommon RA consequence. Objectives: This study aimed to look for cardiac valve involvement in RA patients and determine whether it is linked with disease activity and duration. Methods: Fifty RA patients were recruited consecutively, 5 were males, and 45 were females, aged 27 to 65 years, with a mean of 49.86 ± 9.98. All patients were free from cardiac diseases and underwent entire history, physical examination, laboratory test, and transthoracic echocardiography. The findings were compared to those of age and gender-matched controls, who had no rheumatic and cardiac diseases. Results: Valvular lesions were found in 18 (36%) RA patients, whereas only 2 (4%) of the controls had valvular lesions (p= 0.000063). The most frequently affected valve was the mitral valve 11(61%). There was no relationship between VHD and the duration of the disease, clinical disease activity index (CDAI) score, body mass index (BMI), and smoking. Conclusions: This study has confirmed that VHD (specific to the mitral valve) is significantly higher in RA patients compared with the control sample. There was no correlation between VHD and RA's disease duration, clinical, laboratory, or treatment characteristics.
Keywords: Rheum atoidarthritis; Echocardiography; Valvular heart disease; a case control study